2018
DOI: 10.1186/s12941-018-0293-6
|View full text |Cite
|
Sign up to set email alerts
|

Culture- and PCR-based detection of BV associated microbiological profile of the removed IUDs and correlation with the time period of IUD in place and the presence of the symptoms of genital tract infection

Abstract: ObjectivesThe long-term use of intrauterine devices (IUDs) may lead to biofilm formation on the surface. The aim of this study was to perform the culture- and PCR-based detection of bacteria/fungi from the biofilm of the removed IUDs with different time periods in place.MethodsFor a 2-year period, 100 IUD users were involved in the study. In the majority of the cases, IUDs were removed because of the patients’ complaints. Beside the aerobic and anaerobic culture, species-specific PCR was carried out to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…On the other hand, others found that all examined GBS positive women had vaginal soreness and/or discharge and suggested that streptococci mostly play a secondary role and colonize an already damaged genital epithelium [12]. A very recent Hungarian study examined 100 removed intrauterine devices (57% of the patients showing some type of clinical symptom) and identified the presence of S. agalactiae in 14 cases [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, others found that all examined GBS positive women had vaginal soreness and/or discharge and suggested that streptococci mostly play a secondary role and colonize an already damaged genital epithelium [12]. A very recent Hungarian study examined 100 removed intrauterine devices (57% of the patients showing some type of clinical symptom) and identified the presence of S. agalactiae in 14 cases [13].…”
Section: Introductionmentioning
confidence: 99%
“…Общо 62% от изследваните извадени спирали дават положителен резултат за аеробни и/или анаеробни бактерии. Честотата на полово предаваните инфекции е много ниска, докато микроорганизми, свързани с бактериална вагиноза, са често срещани в пробите от формирания биофилм [11]. В литературата са описани няколко случая на АСИ, обусловени от бактериална вагиноза [12,13], но значението на IUD за развитието на АСИ все още не е изяснено.…”
Section: Fig 1 Us Data For Persisting Iud In the Uterine Cavity And Uterine Wall Of The Patientunclassified
“…A total of 62% of the investigated removed devices had positive culture results for aerobic and/or anaerobic bacteria. While the prevalence of sexually transmitted infections was very low in the investigated low-risk population, species associated with bacterial vaginosis were often found in the biofi lm samples [11]. Several cases of IRA related to bacterial vaginosis have been described [12,13], but the role of IUD-s for the development of infection related arthritis has not been clarifi ed.…”
Section: Fig 1 Us Data For Persisting Iud In the Uterine Cavity And Uterine Wall Of The Patientmentioning
confidence: 99%
“…The condition is characterized by low levels of "healthy" lactobacilli and overgrowth of diverse bacteria from other taxonomic groups, including Gardnerella, Atopobium, Mobiluncus, Prevotella, Bacteroides, Anaerococcus, Peptostreptococcus, Sneathia, Leptotrichia, and members of the class Clostridia, among others (Ravel et al, 2011;Srinivasan et al, 2012). BV has been associated with higher risk of sexually transmitted infections (Wiesenfeld et al, 2003;Brotman et al, 2010;Van De Wijgert, 2017), urinary tract infections (Harmanli et al, 2000;Hillebrand et al, 2002), post-surgical complications (Watts et al, 1990), infertility (Spandorfer et al, 2001), pregnancy losses (Ralph et al, 1999), preterm birth (Svare et al, 2006), intrauterine (Di Paola et al, 2017;Ádám et al, 2018) and intraamniotic infections (Silver et al, 1989), as well as cervical infections, dysplasia, and cancer (Di Paola et al, 2017;Laniewski et al, 2018;Brusselaers et al, 2019). These conditions and health complications associated with BV and its member bacteria can be caused not only by bacteria, but also by eukaryotic (e.g., trichomoniasis) (Jarrett et al, 2019) and viral (e.g., HIV, HSV, HPV) pathogens.…”
Section: Introductionmentioning
confidence: 99%